Identification of Online Educational Game Applications in Teaching English for Madrasah Students - Eka Melati; Fahria Malabar; Alim Hardiansyah; Nursakina Husen; Pandu Adi Cakranegara (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article identified many educational game applications we found online that were relevant for application among madrasa students. Many studies on learning English for madrasah students have been carried out. We have not found any studies with the theme of identifying some relevant game applications applied in madrasah environments whose learning is more Islamic in content and slightly different from other general schools in Indonesia. For this reason, we have conducted a series of data searches in the context of the scientific context of international experts and domestic publications. To get data that can answer the problem first, we conducted a comprehensive study that involved data coding, thorough evaluation, and interpretation of the data so that the data could be used as the highest answer to this elephant's question. After we studied it, we got the results and discussed them carefully. Finally, we can summarize several educational game applications we can access online that we apply to madrasas, including children's pictures dictionary, monkey puzzle game, little birds game, kids learning, Billy playing games, and several games. Another trendy game has been applied in several schools in international contacts. Hopefully, the results of this identification can be helpful in the following study.